Comprehensiveness, Completeness and Objectivity of the Criminal Case Inquiry as Principle of Contemporary Criminal Proceedings - Derishev, Yury V.; Olefirenko, Tatiana G. (Sibirskoe ûridičeskoe obozrenie (Online), 2016)
The authors on the basis of certain Russian science of criminal procedural law positions study concerning ratio of criminal proceedings adversary sources and the provision of complete, comprehensive and objective investigation of the case offer the model of legislative consolidation of the latter as a principle of modern Russian criminal procedural law.